Methodology For Assessing The Production Potential Of Grain Processing Enterprises. - Sotiboldievich, Jalilov Bahrom (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the current economic environment, the assessment of the production potential of enterprises in the field of grain processing plays a crucial role not only in the viability of enterprises in the market, but also in the efficient operation and competitiveness of the entire industry. The article shows that the assessment of the production potential of enterprises in the field of grain processing is one of the most important ideas in terms of effective development of the industry. The proposed assessment methodology was tested on the example of grain processing enterprises in Namangan region.